Social Distancing and SARS-CoV-2 Transmission Potential Early in the Epidemic in Finland - Auranen Kari; Shubin Mikhail; Karhunen Markku; Sivelä Jonas; Leino Tuija; Nurhonen Markku (Lippincott Williams and Wilkins, 2022)
Background:
Information about social mixing patterns under heavy social distancing is needed to model the impact of nonpharmaceutical interventions on SARS-CoV-2 transmission.
Methods:
We conducted a survey on daily person-to-person contacts during the early phase of the SARS-CoV-2 epidemic in Finland, one month after strong social distancing measures had been introduced nationwide. We defined a contact as exchange of at least a few words in proximity of another person. We also considered physical (“skin-to-skin”) contacts separately. Based on 3,171 reported contacts by 1,320 participants of 1–79 years of age, we estimated age-stratified contact matrices essential in modeling virus transmission.
Results:
Compared with contacts during prepandemic conditions, as learned from the Finnish part of the Polymod study, there was a 72% (95% credible interval, CI = 71, 74) reduction in the daily number of all contacts and a 69% (95% CI = 66, 73) reduction in the daily number of physical contacts in April 2020. The largest reduction, of almost 90%, occurred in physical contacts by individuals more than 70 years of age. The estimated reduction in the transmission potential of the virus attributable solely to reduced contact frequencies varied between 59% (whole population; physical contacts; 95% CI = 52, 68) and 77% (over 20-year olds; physical contacts; 95% CI = 70, 89).
Conclusions:
We surmise that the large reduction in the daily numbers of social contacts in the early part of the SARS-CoV-2 epidemic in Finland was likely a major contributor to the steady decline of the epidemic in the country since early April.